Drainage properties of technosols made of municipal solid waste incineration bottom ash and coal combustion residues on potash-tailings piles: A lysimeter study. (10th January 2021) - Bilibio, Carolina; Retz, Stefanie; Schellert, Christian; Hensel, Oliver
Abstract: Mining is one of the most essential economic activities. However, mining produces large volumes of waste. A prominent example is the potash industry, which generates millions of tons of tailings, approximately 90% of which are comprised of sodium chloride. Precipitation events dissolve this sodium chloride and generate saline drainage. To minimize the amount of brine, the University of Kassel, in partnership with the Schmeisky environmental consultancy, is attempting to develop an evapotranspiration cover for potash tailings piles based on technosol application. To further the research in this field and to assess the drainage quality of technosols used for the evapotranspiration cover of mining tailings, one experiment with 8 nonweighing lysimeters was conducted above a potash tailings pile in Heringen, Germany. Lysimeters were filled with four different technosols composed of municipal solid waste incineration bottom ash and coal combustion residues. During three hydrological years, the drainage amount, pH and electrical conductivity were evaluated on a weekly basis. Monthly analyses included the concentrations of chloride, sodium, sulfate, calcium, potassium, nitrate, magnesium and ammonium, as well as chromium, nickel, zinc, copper, lead, cadmium, mercury and arsenic. Overall, it was observed that the pH of the drainage increased, whereas its electrical conductivity decreased due to the leaching of ions. Chemical elements generally decreased to lower limits for waste use. Moreover, higher ionic loads were verified in winter, and technosols with larger proportions of municipal solid waste incineration bottom ash presented higher total ionic loads during the evaluation time of the experiment. Highlights: The chemical properties of the drainage from four technosols were evaluated. Drainage pH increased, and its electrical conductivity decreased. Overall, the chemical elements in the drainage decreased to lower limits for waste use. Higher ionic loads in winter than in summer were verified. Technosols with larger proportions of MSWI had higher total ionic loads.